Care and Maintenance of Landscape Palms in South Florida - Eva C. Worden; Timothy K. Broschat; Charles Yurgalevitch (EDIS)
This document is ENH 866, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 10, 2002.